2007
DOI: 10.1097/blo.0b013e31803d3aad
|View full text |Cite
|
Sign up to set email alerts
|

CASE REPORT: Cefazolin-induced Hemolytic Anemia

Abstract: Antibiotic-induced hemolytic anemia is a rare complication. Prophylactic cephalosporins are widely used in patients having orthopaedic procedures. When there is a precipitous drop in hemoglobin levels, it is important for the clinician to consider the possibility of drug-induced anemia when other causes of blood loss have been excluded. We present a patient with no prior drug allergies who had antibiotic-induced hemolytic anemia develop after total knee arthroplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Cerynik et al reported a case of a 50-year-old man with hemolytic anemia secondary to cefazolin administration for right total knee arthroplasty [ 4 ]. Prophylactic cephalosporin was administered and postoperatively, IV cefazolin was continued, with anemia developing postoperative day 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cerynik et al reported a case of a 50-year-old man with hemolytic anemia secondary to cefazolin administration for right total knee arthroplasty [ 4 ]. Prophylactic cephalosporin was administered and postoperatively, IV cefazolin was continued, with anemia developing postoperative day 1.…”
Section: Resultsmentioning
confidence: 99%
“…However, to our knowledge, a negative DAT does not definitively rule out DIIHA, because there are several drug-induced immune hemolytic anemia mechanisms [ 7 ]. First, the drug can act as a hapten—where antibodies are only detected in the presence of the drug [ 1 , 4 , 8 ]. Second, the drug can elicit an immune response mediated by autoantibodies—antibodies are drug-independent.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Neither medication was taken by our patient; however, about 6 weeks earlier he had been on a cephalosporin for 5 days. Indeed, cephalosporins are known to be potential inducers of clinically significant hemolytic anemia [ 27 30 ].…”
Section: Differential Diagnosismentioning
confidence: 99%